Paweł A. Trzos (2012). Codzienność we wczesnej edukacji muzycznej. Bydgoszcz: Wyd. UKW, ss. 244 (Przegląd Pedagogiczny, 2016)
Recenzja publikacji: Paweł A. Trzos (2012). Codzienność we wczesnej edukacji muzycznej.